Planning of power distribution networks in densely populated cities. Through distributed generation and capacitive compensators - Alarcón Villamil, Jorge Alexander; Rivera Rodríguez, Sergio Raúl; Santamaria Piedrahita, Francisco (Revista Vínculos, 2019)
This paper analyses different options that can be used to solve the problem of the planning of power distribution networks by including capacitive compensation and distributed generation. The methodology for planning aims to determine the size of the units, the bus where the units have to be located, and the year in which investments should be made, in order to minimize the total energy losses on the network during the planning period. The work analyses four different cases: planning using neither capacitive compensation (SC) nor distributed generation (DG), planning using only SC, planning using only DG, and planning using reactive compensation and distributed generation simultaneously. Results show that simultaneous use of SC and DG reduce the total energy losses and improve the voltage profiles on the network, so good results for the planning are obtained.